Búsqueda activa de sintomáticos respiratorios para tuberculosis en población de alto riesgo (2003)
ABSTRACT: An active research on respiratory symptomatic patients was made for the diagnosis of tuberculosis by bacilloscopy in a population of indigents, in prisons and in retirement places foe elders. There were some evident risk factors of tuberculosis like overcrowding, consume of psychoactive substances by indigents and on the men’s prison. The percentage of symptomatic was 18.1% and the average of bacilloscopy for each symptomatic was 1.7. All of the patients with a diagnosis began their treatment. Due to the results, we must recommend an active search of these cases as a viable strategy in high risk populations as well as a constant evaluation of the cost/efficacy in low income neighborhoods.